THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON THE DELAYS OF GOVERNMENT CONSTRUCTION PROJECTS IN WEST PAPUA PROVINCE - Joseph; Anton Soekiman; Chandra Afride Siregar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Construction work is a work that has a complex system because it involves various parties from the pre-contract stage to the post-contract stage so that it often causes problems of delays in completing work which can result in failure to achieve project objectives. This study aims to analyze internal and external factors that influence delays in government projects in West Papua Province, as well as to analyze the impact of these internal and external factors. The study was conducted in the West Papua Province area covering Manokwari Regency, South Manokwari, Arfak Mountains, Fakfak, Kaimana, Bintuni Bay, and Wondama Bay. The research sample was a construction company located in the West Papua Province area which was taken using the Cluster Sampling technique. The internal factor variables observed included financial problems, human resources, materials. The external variables from the government that were observed included design and planning, Government Regulations of the Special Autonomy Law. While the environmental factors observed included weather conditions. The variables of the impact of delays observed included costs, time, payment, scheduling, and productivity. The data collection methods used were interviews, questionnaires, and documentation. Measurement of variables using a Likert scale, and analyzed using the RII (Relative Importance Index) program to determine the dominant factors causing delays in the completion of construction work, and the impacts caused. This study found that the main internal factors influencing the delay of construction projects were delays in the delivery of materials from outside West Papua, and limited budget or working capital affected the smooth implementation of the project. While the main external factors were direct appointments that did not understand the specifications of the work, direct appointments of contractors from Papuan companies who were not competent in carrying out the work, and design changes made in the middle of the project increased the risk of delays. The existence of internal and external factors of delays has an impact on increasing the time needed to complete the project, rescheduling from the specified time, increasing costs used in completing the project, delays in payments, and decreasing productivity/efficiency of the workforce.